Internationally Adopted Children's Reading Comprehension in Second Grade. Issue 3 (2nd July 2016) - Rygvold, Anne-Lise; Theie, Steinar
ABSTRACT: This is a longitudinal study assessing language and literacy skills in internationally adopted children and controls at four years and in second grade at school. The results show small differences between the groups on language skills except for language comprehension at the age of four and reading comprehension in second grade where the adoptees scored significantly lower than their peers did. Significant predictors of the reading comprehension in the second grade were impressive vocabulary for the non-adoptees and letter recognition for the adoptees at the age of four, and decoding skills and expressive vocabulary for both groups in second grade.